Appearance of peanut agglutinin in the blood circulation after peanut ingestion promotes endothelial secretion of metastasis-promoting cytokines. (5th July 2021) - Wang, Weikun; Sindrewicz-Goral, Paulina; Chen, Chen; Duckworth, Carrie A; Pritchard, David Mark; Rhodes, Jonathan M; Yu, Lu-Gang
Abstract: Peanut agglutinin (PNA) is a carbohydrate-binding protein in peanuts that accounts for ~0.15% peanut weight. PNA is highly resistant to cooking and digestion and is rapidly detectable in the blood after peanut consumption. Our previous studies have shown that circulating PNA mimics the actions of endogenous galactoside-binding protein galectin-3 by interaction with tumour cell-associated MUC1 and promotes circulating tumour cell metastatic spreading. The present study shows that circulating PNA interacts with micro- as well as macro-vascular endothelial cells and induces endothelial secretion of cytokines MCP-1 (CCL2) and IL-6 in vitro and in vivo . The increased secretion of these cytokines autocrinely/paracrinely enhances the expression of endothelial cell surface adhesion molecules including integrins, VCAM and selectin, leading to increased tumour cell-endothelial adhesion and endothelial tubule formation. Binding of PNA to endothelial surface MCAM (CD146), via N-linked glycans, and subsequent activation of PI3K-AKT-PREAS40 signalling is here shown responsible for PNA-induced secretion of MCP-1 and IL-6 by vascular endothelium. Thus, in addition to its influence on promoting tumour cell spreading by interaction with tumour cell-associated MUC1, circulating PNA might also influence metastasis by enhancing the secretion of metastasis-promoting MCP-1 and IL-6 from the vascular endothelium. Abstract : Peanut agglutinin is a carbohydrate-binding protein in peanuts that rapidly enters into the blood circulation after peanut consumption. This study shows that circulating peanut agglutinin interacts with the blood vascular endothelium and promotes endothelial secretion of metastasis-promoting cytokines. Frequent consumption of peanuts by cancer patients therefore might increase risk of metastasis.